PSIV-15 Influence of Particle Size of Enogen Feed Corn and Conventional Yellow Dent Corn on Lactating Sow Performance. (7th May 2021) - Williams, Hadley; Tokach, Mike D; Woodworth, Jason C; Goodband, Robert D; DeRouchey, Joel M; Dritz, Steve S; Wecker, Haley; Calderon, Hilda I
Abstract: A total of 107 sows (Line 241; DNA, Columbus, NE) across 4 batch farrowing groups were used to evaluate the effects of corn source and particle size on sow and litter performance. Treatments were arranged in a 2×2 factorial with main effects of corn source (Enogen® Feed corn (Syngenta Seeds, Downers Grove, IL) or conventional yellow dent corn) and ground corn particle size (600 or 900 µm). Sows were blocked by parity and BW upon arrival to the farrowing house. There were approximately 27 sows per treatment, sow was considered the experimental unit, dietary treatment was a fixed effect, and sow group and block were used as random effects. Main effects of corn source and particle size as well as their interactions were tested. From farrowing to weaning, there was a tendency for a source×particle size interaction (P=0.065) for sow BW change. Sows fed 900 µm Enogen Feed corn had decreased BW loss compared to sows fed other treatments which were similar in BW loss. There was a source×particle size interaction (P=0.048) for lactation ADFI with sows fed 900 µm conventional yellow dent corn having lower feed intake than the sows fed 600 µm conventional yellow dent corn, whereas sows fed 900 µm Enogen Feed corn had greater feed intake compared to the sows fed 600 µm Enogen Feed corn. There was a tendency for a particle size main effect (P<0.10) for litter ADG (2, 849 vs 2, 635 g/d) and total litter gain (45.7 vs 42.3 kg), with sows fed corn ground to 600 µm having increased litter ADG and total litter gain compared to sows fed corn ground to 900 µm. In summary, there were few differences in sow or litter characteristics among corn sources. Reducing particle size of both corn sources tended to increase litter ADG and weaning weights.